(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The study shows that the impact of artificial short-cup photoperiod on plants in early stages of development, changes of the aminoacid exchange and the building of morphological elements are kept synchronous in the apical cone of spring wheat shoot.